IRON SUPPLEMENTATION DOES NOT WORSEN RESPIRATORY HEALTH OR ALTER THE SPUTUM MICROBIOME IN CYSTIC FIBROSIS - Gifford, Alex H. (2013)
BACKGROUND: Iron supplementation for hypoferremic anemia could potentiate bacterial growth in the cystic fibrosis (CF) lung, but clinical trials testing this hypothesis are lacking. METHODS: Twenty-two adults with CF and hypoferremic anemia participated in a randomized, double-blind, placebo-controlled, crossover trial of ferrous sulfate 325mg daily for 6 weeks. Iron-related hematologic parameters, anthopometric data, sputum iron, Akron Pulmonary Exacerbation Score (PES), and the sputum microbiome were serially assessed. Fixed-effect models were used to describe how ferrous sulfate affected these variables. RESULTS: Ferrous sulfate increased serum iron by 22.3% and transferrin saturation (TSAT) by 26.8% from baseline (p <0.05) but did not affect hemoglobin, sputum iron, Akron PES, and the sputum microbiome. CONCLUSIONS: Low-dose ferrous sulfate improved hypoferremia without correcting anemia after 6 weeks. We did not observe significant effects on sputum iron, Akron PES, and the sputum microbiome. Although we did not identify untoward health effects of iron supplementation, a larger blinded randomized controlled trial would be needed to fully demonstrate safety.